Recycling and elimination of wastes obtained from agriculture by using nanotechnology: nanosensors - Alvarado, M. A. (2017)
In the friction process of two materials and in the presence of some proper lubricants, the wear process manifest itself as a material transfer from an element of the friction couple on the other, process specific to the selective transfer mechanism. The selective transfer can be sure achieved in a friction couple if there is a favorable energy, the relative movement and if in the friction area is a material made by copper and the lubricant is adequate (glycerin). The selective transfer mechanism is characterized by the physicochemical processes, which take place in the contact zones of the friction couples, and which to allow the selective transfer of some elements of the materials from a surface to the other, forming a thin superficial layer with the superior properties at wear and friction. This is a condition for any friction couple of high efficiently and a normal self-adjusting phenomena. The forming of this layer on the contact surfaces makes as fiction force to be reduced. It is in closely related to the structure formed by the selective transfer, between the metallic friction surfaces and with the properties these surface layers metallic. The most important parameters concerning the physical state of the superficial layers are micro-tensions, the structure and its modification on friction surfaces, the structure defects as well as the way of distribution of the additions and of the alloying elements from alloy. The purpose of the present paper is research these parameters by the structural analysis with X-rays, as the research method of the thin superficial layers.